THE CHARACTERISTICS OF ELECTRON-NUCLEAR MODEL IN THE DEGENERATE DWARFS THEORY. EQUATION OF STATE - Vavrukh, M. V.; Dzikovskyi, D. V. (Одеські астрономічні публікації, 2017)
Within the microscopic theory the ground state energy of spatially homogeneous degenerate relativistic subsystem of electrons in the ﬁeld of stationary nuclei of l-th sorts with charges z1, . . . , zl was calculated. In the two- and three-particle electron correlations approximation the contributions of Coulomb interactions to the equation of model state at low temperatures was analyzed.